2015
DOI: 10.17113/ftb.53.01.15.3633
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity, Mineral Content and Sensory Properties of Gluten-Free Rice and Buckwheat Cookies

Abstract: SummaryLight buckwheat fl our was used to substitute rice fl our at the level of 10, 20 and 30 % to produce gluten-free cookies. The substitution of gluten-free cookie formulation with light buckwheat fl our contributed to the signifi cantly higher mineral content, especially magnesium, potassium, iron and copper, in comparison with the control rice cookies (p<0.05). Gluten-free cookies made with rice fl our and buckwheat fl our exhibited signifi cantly higher total phenolic and rutin content, scavenging activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 31 publications
2
18
0
3
Order By: Relevance
“…Growing interest has been also given to pseudocereals and noncereals flours for their nutritional and phytochemical potential (Table 1). Several works have indicated that the major pseudocereal species (buckwheat (Saka c et al, 2015), amaranth (several species) (Venskutonis & Kraujalis, 2013) and quinoa (Chenopodium quinoa) (Hemalatha et al, 2016)) are rich in Table 1 Phytochemical composition of gluten-free matrices Total polyphenols (mg GAE g À1…”
Section: Other Gluten-free Cereals Pseudocereals and Noncereals Matrmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing interest has been also given to pseudocereals and noncereals flours for their nutritional and phytochemical potential (Table 1). Several works have indicated that the major pseudocereal species (buckwheat (Saka c et al, 2015), amaranth (several species) (Venskutonis & Kraujalis, 2013) and quinoa (Chenopodium quinoa) (Hemalatha et al, 2016)) are rich in Table 1 Phytochemical composition of gluten-free matrices Total polyphenols (mg GAE g À1…”
Section: Other Gluten-free Cereals Pseudocereals and Noncereals Matrmentioning
confidence: 99%
“…or sorghum(Licata et al, 2014) flours presented certain technological limitations because these flours notably changed the appearance, colour, texture, aroma and taste of gluten-free products, which can easily impair consumer acceptability. The addition of pseudocereal flours such as buckwheat(Saka c et al, 2015), amaranth(Chauhan et al, 2015) or quinoa(Jan et al, 2016) may give gluten-free baked products with enhanced contents of total phenolic compounds and antioxidant activity, with good effect on their quality and acceptability. Janet al (2016) highlighted the actual trend towards germinated flours to increase the antioxidant capacity of final products.…”
mentioning
confidence: 99%
“…In addition, it is characterised by high content of valuable protein with a biological value equivalent to 93% of defatted milk and 81.5% of egg protein as well as high content of minerals, organic acids, vitamins, resistant starch, total and soluble dietary fibres and polyphenols (Gambu s et al, 2009). Buckwheat flour has a strong flavour due to the presence of phenolic compounds which can enhance the organoleptic properties and improve the flavour (Saka c et al, 2015). The evaluation of buckwheat-supplemented cookies (30; 40; 50% of wheat flour) showed improved organoleptic properties in comparison with control wheat cookie (Filip cev et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Rice, on the other hand, is the common flour used in many GF formulations due to its bland taste, white colour and highly digestible carbohydrates . The mixture of rice and buckwheat flours has already been tested for the production of cookies in terms of sensorial properties (Torbica et al, 2012;Saka c et al, 2015). A blend of rice and buckwheat flours (90/10; 80/20; 70/30) showed good results giving significantly higher scores for almost all the tested sensorial attributes when compared to wheat-based samples (Torbica et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous researchers have been working on the development of gluten-free products by the substitution of wheat floor with different gluten-free cereal flours such as those from rice [63][64][65], acorn [66,67], soybean [68], sorghum [69][70][71] or mixtures [72][73][74]. Other studies have evaluated wheat flour replacement by pseudo-cereals such as amaranth [75][76][77][78], quinoa [79][80][81], buckwheat [78,[82][83][84] or legume flours [85][86][87][88][89].…”
Section: Substitution Of Proteinsmentioning
confidence: 99%